Unlocking the potential: addressing challenges faced by women's cooperatives in Malaysia / Leviana Andrew and Norashikin Shariffuddin - Andrew, Leviana; Shariffuddin, Norashikin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The success of cooperative businesses heavily relies on how well the government supports them. Recent studies have been all about this, emphasizing how crucial it is for the government to come up with effective policies that actually work. And by effective, it means they must get stuff done even when resources are tight. Government effectiveness basically boils down to how good they are at making and putting into action these policies. But here's the kicker: sometimes what the government thinks cooperatives need and what they actually need do not quite match up. Studies have shown that training programs and subsidies don't always hit the mark when it comes to boosting cooperative performance. Even in countries like Vietnam and China, where they've tried to give cooperatives a leg up, there's been a disconnect between the support offered and what cooperatives really require.